The Combination of AFP and “Up-To-Seven” Criteria May Be a Better Strategy for Liver Transplantation in Chinese Cirrhotic HCC Patients - Zhang, Da-li; Feng, Dan-ni; He, Xi; Zhang, Xiao-feng; Li, Li-xin; Li, Zhi-jie; Niu, Xiao-feng; Zhuang, Yun-long; Liu, Zhen-wen; Gao, Xu-dong; Wang, Hong-bo (Frontiers in Oncology, 2022)
Background: Orthotopic liver transplantation (OLT) is a life-saving option for patients with hepatocellular carcinoma (HCC), but the expanded OLT criteria remain controversial. Objective: The study aimed to explore whether expanded OLT criteria can be applied to Chinese cirrhotic patients with HCC. Methods: This retrospective study analyzed risk factors for HCC recurrence and death and compared patients’ tumor characteristics and outcomes in groups of Milan, “Up-to-seven”, and Hangzhou criteria, and groups between met and unmet the combinative criteria of “Up-to-seven” and AFP of < 1000 ng/mL. Results: Among 153 patients who underwent OLT for HCC in four years of follow-up, 20 (13.1%) patients had HCC recurrence, and 11 (7.2%) had HCC-related death. Multivariate Cox regression analysis showed that preoperative alpha-fetoprotein (AFP) of > 1000 ng/mL (Hazard ratio [HR]: 10.05, 95% confidence interval [CI]: 2.45–41.13, P = 0.001) was independent risk factor for HCC recurrence and HCC-related death (HR: 6.63, 95%CI: 1.31–33.52, P = 0.022). Patients who did not meet Milan criteria but satisfied the “Up- to-seven” criteria had no differences in overall survival (OS) (P = 0.68) and disease-free survival (DFS) (P = 0.35) than patients who met the Milan criteria. The combination of “Up-to-seven” criteria and AFP of < 1000 ng/mL differed significantly (HR: 18.9; 95% CI: 4.0–89.2; P < 0.001). Patients with HCC who met the “Up-to-seven” criteria and AFP of < 1000 ng/mL (n = 121) had excellent survival with fourth-year OS of 90.7% (P < 0.001) and DFS of 90.8% (P < 0.001), which is significantly better compared to the other group (n = 32) (OS of 64.4% and DFS of 48.8%) and patients who met the Milan criteria (n = 108, OS of 87.7%, DFS of 89.6%), allowing 28.9% (13/45) of patients who did not meet the Milan criteria to benefit from OLT. Conclusion: Chinese cirrhotic patients with HCC who met the combinative criteria of “Up-to-seven” and AFP of < 1000 ng/mL had better survival than those who met the Milan criteria, and these combinative criteria benefited more patients and may become a better option for OLT.